Bringer of Sorrow: the characterization of Penthesilea in Quintus' Posthomerica 1 - De Almeida Semedo, Rafael (2023)
Drawing on the narratological concept of characterization, this paper addresses the portrayal of Penthesilea, the queen of the Amazons, in Quintus of Smyrna’s Posthomerica, Book 1 (ca. 3 AD). This late antique epic is a 14-Book iteration in dactylic hexameter of the events that take place between the Iliad and the Odyssey, such as the death of Achilles, the Trojan horse, and the sack of Troy. After the death of Hector in the Iliad, a series of surrogates appear in the Posthomerica to substitute him as the bulwark of Priam’s army, all of which eventually die. In Book 1, the Amazonomachy, Penthesilea fills this temporary role, assuming the position of a protagonist who arrives to lift the Trojan spirits and lead them back into the fight, but who is then killed by Achilles in combat towards the end of the chapter. I aim to assess the strategies of the Quintean narrator in presenting the first protagonist of his epic, balancing the characterization of her beauty and her martial prowess as a female warrior. I also address the importance of Penthesilea, whose telling name can be interpreted as “the one who brings sorrow (to the people?)”, for the narrative structure of the poem in three levels: a) in Book 1, the Amazonomachy; b) in Books 1-5, the Achilleid; and c) in Books 1-14, the poem as a whole.